Serotonin 2C Receptor (5-HT2CR) mRNA Editing-Induced Down-Regulation of 5-HT2CR Function in Xenopus Oocytes: the Significance of Site C Editing - Michihisa Tohda; Pham T.N. Hang; Naofumi Kobayashi; Kinzo Matsumoto (Elsevier, 2010)
Serotonin 2C receptor (5-HT2CR) mRNA receives editing at 5 nucleotide positions (sites A - E) located in the sequence encoding the second intracellular loop of 5-HT2CR. 5-HT2CR mRNA without editing and with editing at sites AB, ABD, ABC, ABCD, and C are translated to 6 isoforms of 5-HT2CR: INI(non-edited), VNI(AB), VNV(ABD), VSI(ABC), VSV(ABCD), and ISI(C), respectively. In this study, we investigated electrophysiologically the ability of these isoforms to couple with the G protein / phospholipase C (PLC) system using Xenopus oocytes injected with edited 5-HT2CR RNAs and muscarinic M1 receptor (M1R) RNA. The efficacy with which 5-HT stimulated each isoform was calculated by comparing 5-HT-induced current with 100 μM acetylcholine-induced M1R current. Stimulation with 5-HT of INI(non-edited), VNI(AB), VNV(ABD), VSI(ABC), VSV(ABCD), and ISI(C) expressed in Xenopus oocytes showed concentration-dependent responses with EC50 values of 8.6, 17.2, 76,5, 22.0, 91.2, and 20.3 nM, respectively. No significant difference in the ability of 5-HT to induce currents among the oocytes expressing these isoforms was detected, but in the oocytes expressing VSI(ABC) or VSV(ABCD), 5-HT had a significantly reduced ability to induce currents. These results suggest that editing at site C together with sites A and B and/or D markedly reduces 5-HT2CR function by generating isoforms with reduced ability to activate PLC. Keywords:: RNA editing, serotonin 2C receptor subtype, phospholipase C, Xenopus oocyte